EFL Students’ Perspectives on VR-Mediated EAP in the Indonesian Higher Education Settings: A Qualitative Case Study - Dana Kristiawan; Lilik Istiqomah (STKIP AGAMA HINDU SINGARAJA, 2025)
This qualitative case study investigates how Virtual Reality (VR) mediates English for Academic Purposes (EAP) in a History course from the standpoint of Indonesian EFL undergraduates. Thirty students at a public university in East Java participated in a two-session VR sequence of short 360° “field trips” followed by evidence-anchored speaking and writing. informed by disciplinary literacy in History and genre-based EAP pedagogy. Data were generated through non-participant classroom observations, semi-structured interviews, and brief open-ended reflections. Data were analyzed using reflexive thematic analysis. Findings indicate predominantly positive attitudes toward VR-mediated EAP in the Indonesian higher education setting. Students reported that VR sharpened attention to historical features, supplied shared visual evidence that made discussion more purposeful, and supported movement from description to interpretation and evaluation in short academic products. Learners perceived gains in discipline-relevant lexis (materials/condition, spatial relations, chronology) and increased willingness to speak when guided-noticing prompts and sentence stems were available. Reported constraints, brief motion discomfort, bandwidth/device interruptions, and elevated cognitive effort at the moment of articulation were mitigated by short viewing segments, a one-minute reset, and role rotation during device sharing. The study concludes that, when braided with genre-aware scaffolds, VR functions as a practical mediational tool for fostering participation, clarity of ideas, and discipline-specific vocabulary in History-oriented EAP within Indonesian higher education.